Dietary Supplements Challenges and Future Research - Venketeshwer Rao, A.; Rao, Leticia (IntechOpen, 2023)
Traditionally, nutritional supplements were limited to essential vitamins and minerals. However, in recent years, scientists have identified several biologically active compounds from plant and animal foods having beneficial health effects. Although technically they are not "nutrients," they are referred to as phytonutrients, nutraceuticals, and functional ingredients due to their potential health benefits. Taking advantage of these scientific findings, manufacturers now include supplements in their commercial products. Recognizing the increasing role of nutritional supplements in the management of health, and as more new information becomes available, this book caters to the needs of consumers, health professionals, and regulatory agencies. It covers a range of topics in supplements, from definitions to sources to mechanisms of action to management of health and diseases as well as future challenges. This book is a valuable source of information in this important and fast-growing area of human health.